Comparative Study of Enzyme Linked Immunosorbant Assay and Agglutination Tests in the Diagnosis of Human Brucellosis in Baghdad (Iraqi Journal of Medical Sciences, 2016)
Background:Human infection with Brucella spp. had been able to evoke humeral immune response containing both IgG and IgM.Objective:This study designed to compare results obtained from Rose Bengal Test (RBT), Tube Agglutination Test (TAT) and Enzyme Linked Immunosorbent Assay (ELISA) employ serum are described and compared for the detection of human IgG and IgM anti-brucella antibodies.Methods:Serum samples from 105 subjects were collected. 90 were clinically infected with human brucellosis, and 15 were age and gender matched controls. RBT and TAT are the two screening tests routinely recognized, while the 2-mercaptoethanol test (2ME) is the confirmatory assays currently in use. In order to improve the serological diagnosis of human brucellosis, an indirect IgG, IgM and IgG-IgM ELISA kits were evaluatedResults:Totally, 90 cases were positive in RBT, from those only 92% shows positive TAT, and by ELISA there are IgG (27.78%), IgM (14.44%) and (57.78%) were Positive for both immunoglobulins.Conclusion:Although RBT and TAT are widely applied tests, they cannot differentiate acute and chronic states of brucellosis. Our data suggest that IgM ELISA may be a suitable test for diagnosis acute brucellosis.Keywords :Brucellosis, ELISA, Tube Agglutination.
Keywords: Brucellosis; ELISA; Tube Agglutination